Epistemic Roots, Universal Routes and Ontological Roofs of African “Ritual Archives”: Disciplinary Formations in African Thought - Oluwatoyin Vincent Adepoju (Yoruba Studies Review)
One may compose an essay on another essay, and possibly an even longer one than the essay being studied, long as that one is, when one is confronted with one of those things one has to say something about after encountering them. “Ritual Archives”, the climatic conclusion of the account in The Toyin Falola Reader ( Austin: Pan African University, 2018), of the efforts of Africa and its Americas Diaspora to achieve political, economic, intellectual and cultural individuality, is a deeply intriguing, ideationally, structurally and stylistically powerful and inspiring work, rich with ideas and arresting verbal and visual images. His focus is Africa and its Diaspora, but his thought resonates with implications far beyond Africa, into contexts of struggle for plurality of vision outside and even within the West, the global dominance of whose central theoretical constructs inspires Falola’s essay. “Ritual Archives”, oscillates between the analytical and the poetic, the ruminative and the architectonic, expressive styles pouring out a wealth of ideas, which, even though adequately integrated, are not always adequately elaborated on. This essay responds to the resonance of those ideas, further illuminating their intrinsic semantic values and demonstrating my perception of the intersections of the concerns they express with issues beyond the African referent of “Ritual Archives”. This response is organized in five parts, representing my understanding of the five major thematic strategies through which the central idea is laid out and expanded. 316 Oluwatoyin Vincent Adepoju The first section, “Developing Classical African Expressions as Sources of Locally and Universally Valid Theory” explores Falola’s advocacy for an expanded cultivation of theory from Africa created and Africa inspired expressive forms. “Epistemic and Metaphysical Integrity in Ifá”, the second part, examines his argument for a re-centering of studies in classical African thought within the epistemic and metaphysical frames of those bodies of knowledge, using the Yoruba origin Ifá system of knowledge, spiritual development and divination as an example, an illustration I analyze through my own understanding of the cognitive and metaphysical framework of Ifá. The third unit, “Falola’s Image Theory and Praxis, Image as Archive, Image as Initiator”, demonstrates Falola’s dramatization of the cognitive possibilities of works of art as inspirers of theory, exemplified by a figurine of the Yoruba origin òrìṣà cosmology, the deity Esu. This is the most poetic and one of the most imaginatively, ideationally evocative and yet tantalizingly inadequately elaborated sections of “Ritual Archives”, evoking continuities between Yoruba philosophy, òrìṣà cosmology and various bodies of knowledge across art and image theory and history, without expanding on the ideas or building them into a structure adequately responsive to the promise of the ideas projected, a foundation I contribute to developing by elucidating my understanding of the significance of the ideas and their consonance with related conceptions and issues from Asian, Western and African cultures. I also demonstrate how this section may contribute to clarification of the nature of Yoruba philosophy understood as a body of ideas on the scope of human intelligibility and the relationship between that philosophy and òrìṣà cosmology, an expansive view of the cosmos developed in relation to the philosophy. This is a heuristic rather than an attempt at a definitive distinction and is derived from the relationship between my practical and theoretical investigation of Yoruba epistemology and Falola’s exploration, in “Ritual Archives”, of a particularly strategic aspect of òrìṣà cosmology represented by Esu. The distinction I advance between Yoruba philosophy and òrìṣà cosmology and the effort to map their interrelations is useful in categorizing and critically analyzing various postulates that constitute classical Yoruba thought. This mapping of convergence and divergence contributes to working out the continuum in Yoruba thought between a critical and experiential configuration and a belief system. The fourth section, “The Institutional Imperative”, discusses Falola’s careful working out of the institutional implications of the approach he advocates of developing locally and universally illuminating theory out of endogenous African cultural forms. The fifth part, “Imagistic Resonance”, presents Falola’s effort to make the Toyin Falola Reader into a ritual archive, illustrating his vision for African art as an inspirer of theory, by spacing powerful black and white pictures of forms of this art, mainly sculptural but also forms of Epistemic Roots, Universal Routes and Ontological Roofs 317 clothing, largely Yoruba but also including examples from other African cultures, throughout the book. Except for the set of images in the appendix, these artistic works are not identified, nor does the identification of those in the appendix go beyond naming them, exclusions perhaps motivated by the need to avoid expanding an already unusually big book of about 1,032 pages of central text. I reproduce and identify a number of these artistic forms and briefly elaborate on their aesthetic force and ideational power, clarifying the theoretical formations in which they are embedded and exploring the insights they could contribute to theory beyond their originating cultures. “Ritual Archives” is particularly important for me because it elucidates views strategic to my own cognitive explorations and way of life but which I have not been able to articulate with the ideational comprehensiveness and analytical penetration Falola brings to the subject of developing theory from endogenous African cultural expressions, exemplified by Ifá and art, two of my favorite subjects